Analisis Bibliometrik Pajak Minuman Berpemanis dalam Kemasan (MBDK) - Kezia Rahmawati Santosa; Imam Yuadi (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Packaged sweetened drinks are drinks that have been processed and packaged, which usually contain added sweeteners such as sugar, corn syrup, or sugar substitutes such as aspartame, sucralose, or stevia. This study aims to analyze the development of taxes on packaged sweetened drinks. The data were obtained from a database published by Scopus from 2013 to 2023. The keywords used to obtain results that are in accordance with the bibliometric research are sugar sweetened beverages tax. The bibliometric data analyzed and visualized using VosViewer obtained 2658 keywords, there were 254 keywords that match the requirements on the display of sweetened drink tax, and there were 17337 links or the number of relationships in the visualized data. In addition, this analysis also uses biblioshiny with wordcloud visualization of themes or subjects that are connected to sugar sweetened beverages.